Reduction in seroprevalence of viral transfusion‐transmitted infections in southwest Nigeria in children with sickle cell disease using an enhanced screening strategy. (19th June 2022) - Ogbenna, Ann A.; Akinsete, Adeseye M.; Kalejaiye, Olufunto O.; Matthew, Oyewole Kunmi; Sharma, Deva; Andrews, Jennifer; Kassim, Adetola A.
Summary: Blood transfusion is an integral component in the management of children and adults with sickle cell disease (SCD). Concerns about blood safety due to the high risk of bloodborne infections in sub‐Saharan Africa limits the application of this cost‐effective strategy in the management of individuals with SCD. In a single‐centre, retrospective, longitudinal study in southwest Nigeria, we hypothesised that the use of stringent blood donor selection, along with very sensitive enzyme‐linked immunosorbent assay (ELISA) screening methods would reduce transfusion‐transmitted infections (TTIs). Among 45 002 eligible blood donors at the Lagos University Teaching Hospital in Nigeria, over a 5‐year review period (2015–2019), the seroprevalence rate of viral TTIs was 9.83%. The seroprevalence rates for human immunodeficiency, hepatitis B, and hepatitis C viruses were 1.37%, 6.2%, and 2.25% respectively. Among 172 children with SCD, 71% (122/172) on regular blood transfusion and 29% (50/172) who had never been transfused or had less than two transfusions per lifetime, none acquired any TTIs using our enhanced screening approach during the study period. Thus, safe blood transfusion practices can be provided for children with SCD in sub‐Saharan Africa with the use of stringent donor selection protocols and fourth‐generation ELISA kits for TTI screening.